2014
DOI: 10.1371/journal.pone.0099664
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Stolen Generations' of Mothers and Daughters: Child Apprehension and Enhanced HIV Vulnerabilities for Sex Workers of Aboriginal Ancestry

Abstract: ObjectivesThe number of children in care of the state continues to grow in BC, Canada with a historical legacy of child apprehension among criminalized and marginalized populations, particularly women of Aboriginal ancestry and sex workers. However, there is a paucity of research investigating child apprehension experiences among marginalized mothers. The objective of the current analysis is to examine the prevalence and correlates of child apprehensions among female sex workers in Vancouver, Canada.MethodsAna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Our finding that sex workers avoided accessing services for fear of having their children taken away (apprehended) by children protection services is not unwarranted, considering 37% of sex workers in our study reported ever having a child apprehended, and 38% had been apprehended themselves as children (Duff et al, 2014). These high rates of child apprehension may be owing to the multiple vulnerabilities faced by sex workers (e.g., poverty, homelessness, addiction), as well as child protection workers enforcing laws and regulations that associate parental sex work with placing their children at harm for sexual abuse or exploitation(Barnett, 2008).…”
Section: Discussionmentioning
confidence: 57%
“…Our finding that sex workers avoided accessing services for fear of having their children taken away (apprehended) by children protection services is not unwarranted, considering 37% of sex workers in our study reported ever having a child apprehended, and 38% had been apprehended themselves as children (Duff et al, 2014). These high rates of child apprehension may be owing to the multiple vulnerabilities faced by sex workers (e.g., poverty, homelessness, addiction), as well as child protection workers enforcing laws and regulations that associate parental sex work with placing their children at harm for sexual abuse or exploitation(Barnett, 2008).…”
Section: Discussionmentioning
confidence: 57%
“…Indigenous peoples have a long history of mistrust of health and social services, which has been an ongoing feature of colonization and elements of which continue to this day [ 105 ]. Therefore, involvement of Indigenous peoples in HIV prevention and treatment programs is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Another impact of colonization reflects the concerning trend of the apprehension of children from Indigenous women particularly those considered marginalized due to experiences in sex work or substance use (Duff et al 2014). We utilized the parental stress scale to assess stress levels of the mothers in our study; although it does not capture specific events such as child apprehension, it does capture the desire and intentions of being the ideal mother.…”
Section: Discussionmentioning
confidence: 99%